2016
DOI: 10.1051/ocl/2016022
|View full text |Cite
|
Sign up to set email alerts
|

A chemical platform approach on cardanol oil: from the synthesis of building blocks to polymer synthesis

Abstract: -This review proposes a platform approach for the synthesis of various building blocks from cardanol oil in one or two-steps synthesis. Cardanol is a natural phenol issued from Cashew nutshell liquid (CNSL). CNSL is a non-edible renewable resource, co-produced from cashew industry in large commercial volumes. Cardanol is non-toxic and particularly suitable as an aromatic renewable resource for polymers and materials. Various routes were used for the synthesis of di-and poly-functional building blocks used ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Nevertheless, residual ethylenic protons were detected since the epoxidation conversion was close to 85% and was calculated using i, h, g signals between4.95 and 5.88 ppm. The differentiation of terminal (Hi and Hg) and ethylenic protons along the alkyl and fatty chains demonstrated the lower epoxidation conversion of terminal unsaturations (55%) than internal ones (94%) as previously reported by Jaillet and al [32].…”
supporting
confidence: 83%
“…Nevertheless, residual ethylenic protons were detected since the epoxidation conversion was close to 85% and was calculated using i, h, g signals between4.95 and 5.88 ppm. The differentiation of terminal (Hi and Hg) and ethylenic protons along the alkyl and fatty chains demonstrated the lower epoxidation conversion of terminal unsaturations (55%) than internal ones (94%) as previously reported by Jaillet and al [32].…”
supporting
confidence: 83%
“…It was demonstrated that the high reactivity of the vinyl group of the acrylate monomers based on plant oils determines the course of their polymerization and copolymerization by a free radical mechanism [ 21 ]. Caillol et al [ 22 , 23 ] proposed methods for the synthesis of a new monomer from cardanol ( Figure 2 ), which is isolated from cashew nuts. Reactivity of the cardanol-based monomer in the copolymerization reactions with the POBMs was studied [ 24 ].…”
Section: Features Of Synthesis Of Vinyl Monomers From Plant Oilsmentioning
confidence: 99%
“…In the study [ 23 ], synthetic pathways to molecular blocks from cardanol by one- or two-stage methods were reported. In particular: 1) dimerization/oligomerization of cardanol, to increase its functionality; 2) synthesis of reactive amines by thiolene coupling; 3) epoxidation and (meth)acrylation of cardanol for the synthesis of polymers and materials with oxirane or (meth)acrylate groups.…”
Section: Features Of Synthesis Of Vinyl Monomers From Plant Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 90% of the epoxy resin in the world is still made from BPA. [22,23] Anticipated shortages of petroleum and increasing concerns about the environmental safety and sustainability of its use have led researchers in academia and industry to examine ways of developing polymers from renewable resources. [24] Epoxy resins are already being produced commercially from plant oils.…”
Section: Introductionmentioning
confidence: 99%